2013
DOI: 10.1155/2013/342802
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Acylation-Stimulating Protein Are Strongly Predicted by Waist/Hip Ratio and Correlate with Decreased LDL Size in Men

Abstract: The association of abdominal obesity with cardiovascular risk is often linked to altered secretion of adipose-derived factors and an abnormal lipid profile including formation of atherogenic small dense low density lipoprotein particles (sdLDL). Acylation-stimulating protein (ASP) is an adipose-derived hormone that exhibits potent lipogenic effects. Plasma ASP levels increase in obesity; however, the association of ASP levels with body fat distribution is not yet established, and no study to date has investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
3
6
0
1
Order By: Relevance
“…Contrary to GGT, bilirubin was found to be a powerful antioxidant in vitro and in vivo [57]. In the controls, a positive correlation of plasma ASP with TG levels was found as previously reported [20, 58, 59] although an association with liver enzymes was not detected. …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Contrary to GGT, bilirubin was found to be a powerful antioxidant in vitro and in vivo [57]. In the controls, a positive correlation of plasma ASP with TG levels was found as previously reported [20, 58, 59] although an association with liver enzymes was not detected. …”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, the findings may also reflect increased ASP levels as a result of tissue resistance and together with insulin resistance may exacerbate the dyslipidemic state. The concept of ASP resistance was proposed in several previous studies [16, 58, 59]. In summary, the findings suggest that ASP may play a unique role in the progression of adverse cardiovascular events, independent of insulin.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, most of the recruited patients with MI in the present study were associated with hypertension, DM, high BMI, and dyslipidemia which may explain the elevated ASP levels in the current study that supported by Saleh et al' study that revealed an associations with high ASP levels and obesity, LDL, TG level, and waist/hip ratio which is the main predictor of ASP level. [18] Indeed, elevated ASP levels in acute MI strongly predicted by obesity and dyslipidemia due to overproduction of ASP as consequence of ASP resistance, since ASP resistance causing metabolic alterations and lipid changes which contributed to the formation of atherogenic LDL that encourage AI and incidence of acute MI, [19] this may explain the elevated CRR and AI in association with high ASP levels in patients with acute MI of the present study. In addition, ethnic difference in ASP levels showed by Scantlebury-Manning et al study that pointed out to the higher levels of ASP in Caucasian due to higher TG fasting levels and ASP resistance compared to the other ethnic population that associated with low fasting TG level and higher ASP sensitivity, [20] these findings are in agreement with finding of the present study since; all of enrolled patients were Caucasian that associated with high ASP levels.…”
Section: Discussionmentioning
confidence: 54%
“…Plasma ASP levels were correlated with decreased LDL size in Omani men determined by gradient gel electrophoresis ( 28 ). In line with this, age-adjusted ASP levels were positively associated in men with Lp(a) levels, mediated by increments in SHBG.…”
Section: Discussionmentioning
confidence: 99%